Unveiling mediastinal pathology: role of EUS guided fine needle aspiration in diagnosing mediastinal lesions - S., Mukundan; Venkatakrishnan, L.; R., Vishnu Abishek (International Journal of Research in Medical Sciences, 2018)
Background: Mediastinal lesion is the focus of investigation in diagnosis of infective, granulomatous or neoplastic pathology of respiratory system. Metastatic mediastinal node assessment is an integral part of oncological management. EUS provides access to sampling of mediastinal mass, sub-carinal and aorto-pulmonary nodes. This study aims to assess the clinical impact, diagnostic yield and safety of EUS guided FNA for mediastinal lesions. Methods: Retrospective analysis of prospectively collected data of 72 cases of mediastinal lesions between January 2014 and December 2017 was done. EUS-FNA was performed with a linear echoendoscope using a 22- or 25-gauge needle. Adequacy of cellularity was assessed by on site pathologist. Patient data (demographics, intervention and follow-up) were prospectively collected and introduced in a predefined computer database for later review. Results: EUS-FNA was performed from 57 lymph nodes and 15 mediastinal masses. Adequate samples were obtained in 67 of 72 patients (93.05%). All mediastinal masses were malignant and were identified in the 3rd, 5th and 6th decade of life. Of the 57 lymph nodes, 15 were malignant, 28 had granulomatous lymphadenitis of which 16 individuals became asymptomatic after anti tubercular therapy. Sample was inadequate in 5 circumstances. No major complications were encountered with the procedure in any of the individuals. Conclusions: EUS guided tissue diagnosis is a safe technique and our data supports the use of EUS-FNA in work-up of mediastinal lesions. It is minimally invasive, accurate and has easy access to mediastinum. It has significant impact on patient diagnosis, management and should be considered over other invasive techniques.